About stability analysis of elastic frames - L.M. Kagan-Rosenzweig (Инженерно-строительный журнал, 2012)
This article illustrates a simple method of stability analysis for elastic frames loaded with dead and follow forces. In its undisturbed state, frame elements might undergo not compression only but bending and torsion as well. It is shown that for simple frames there is no necessity of program complexes using.For conservative systems the problem is formulated as a problem of equilibrium bifurcation. For non-conservative systems, dynamical approach is applied. The suggested method is used for calculation of coefficients in equations of motion.